Subventionen in der Bundesrepublik Deutschland: Bestandsaufnahme und Bewertung - Alfred Boss; Astrid Rosenschon (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The extent and the structure of subsidies (including tax concessions) in the Federal Republic of Germany are analyzed. Subsidies per unit value added increased significantly after German reunification and declined only moderately in 1995. Nevertheless, the subsidies (comprehensively defined) reached roughly 8.6 p.c. of GDP.
Keywords: H19; 330; Subsidies; Tax expenditures; Subvention; Steuerbegünstigung; Deutschland